Method for the construction of the Lewis-Riesenfeld time-dependent invariants and their eigenvalue equations - De Ponte, M. A. [UNESP]; Cônsoli, P. M.; Moussa, M. H.Y. (American Physical Society (APS), 2018)
We propose here a method for the construction of the Lewis and Riesenfeld time-dependent invariants. Instead of directly invoking the equation that defines the invariant associated with a time-dependent Hamiltonian, our method allows the step-by-step construction of the invariant as a product of operators, and mainly a straightforward derivation of its eigenvalue equation.